2019
DOI: 10.3389/fphar.2019.00771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antiarrhythmic Drugs on the Outcome of Short QT Syndrome

Abstract: Short QT syndrome (SQTS) is associated with sudden cardiac arrest. There are limited data on the impact of antiarrhythmic drugs on the outcome of SQTS. Materials and Methods: We studied data that describe the clinical outcome of 62 SQTS patients treated with antiarrhythmic drugs, who were recruited from a pool of patients diagnosed in our institution and also from known databases after a systematic search of the published literature. Results: Sixty-two SQTS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The therapeutic approaches for SQTS are challenging for physicians because of the low prevalence and rare cases. Until now, a small number of drugs including disopyramide, nifekalant, quinidine, flecainide, sotalol, ibutilide and propafenone have been tested by in vivo studies on SQTS1 (Abriel and Rougier, 2013), among which only quinidine has shown profit effect in the treatment (Mizobuchi et al, 2008;Giustetto et al, 2011;Mazzanti et al, 2017;El-Battrawy et al, 2019). In human-induced stem cell-derived cardiomyocytes (hiPSC-CMs) from a patient with SQTS type 1, besides quinidine, disopyramide, ajmaline, ivabradine and mexiletine but not sotalol, amiodarone, flecainide and ranolazine showed profitable (APD-prolonging and antiarrhythmic) effects (Shinnawi et al, 2019;Zhao et al, 2019;Lan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic approaches for SQTS are challenging for physicians because of the low prevalence and rare cases. Until now, a small number of drugs including disopyramide, nifekalant, quinidine, flecainide, sotalol, ibutilide and propafenone have been tested by in vivo studies on SQTS1 (Abriel and Rougier, 2013), among which only quinidine has shown profit effect in the treatment (Mizobuchi et al, 2008;Giustetto et al, 2011;Mazzanti et al, 2017;El-Battrawy et al, 2019). In human-induced stem cell-derived cardiomyocytes (hiPSC-CMs) from a patient with SQTS type 1, besides quinidine, disopyramide, ajmaline, ivabradine and mexiletine but not sotalol, amiodarone, flecainide and ranolazine showed profitable (APD-prolonging and antiarrhythmic) effects (Shinnawi et al, 2019;Zhao et al, 2019;Lan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Risk stratification and valid pharmacological therapies have not yet been established due to the low number of patients with SQTS [ 2 ]. Quinidine, which blocks several potassium channels including I to and I Kr , was reported to prolong the QT interval and reduce the incidence of life-threatening arrhythmias in patients with SQTS [ 85 , 86 ]. Other antiarrhythmic drugs, such as sotalol, amiodarone, disopyramide, and β-blockers, failed to show beneficial effects on SQTS [ 86 ].…”
Section: Lqts and Sqtsmentioning
confidence: 99%
“…Until now, there has been very limited research to test drug effects in SQTS patients. A few anti-arrhythmic drugs such as disopyramide, quinidine, sotalol, ibutilide have been tested in SQT1 patients, but only quinidine has been shown to be effective in the treatment [5].…”
Section: Introductionmentioning
confidence: 99%